Unlocking the Secret to a Restful Night's Sleep: Understanding Insomnia (Anidra) and Overcoming it with Ayurveda (International Journal of Ayurveda and Pharma Research, 2023)
Sleep is a naturally occurring state of both mind and body. The challenge of insomnia disorder arise when an individual subjectively perceives or subpar sleep quality. This can manifest in various ways, including difficulty initiating sleep, frequent nighttime awakenings with subsequent struggles to return to slumber, premature morning awakenings. Insomnia is intimately linked to various medical and psychiatric conditions and can have profound repercussions on an individual's overall quality of life and emotional well-being. Regrettably, in our contemporary world, a growing number of individuals have become reliant on sleep-inducing medications, forming habitual dependencies on them. Within the framework of holistic well-being, three essential pillars support a healthy life: Aahar (nutrition), Nidra (sleep), and Brahmcharya (celibacy or responsible sexual conduct). Nidra, plays a crucial role in nourishing the living body. Anidra, the absence of sound sleep, has been meticulously described by ancient scholars in various contexts, such as its connection to Vata Nanatmaja Vikara and Vataja Jwara. Traditional Ayurvedic therapies, known as Panchkarma, offer effective approaches to address Anidra. These therapies include Shirodhara (a continuous stream of warm oil on the forehead), Shirobasti (retaining oil on the head), Shiroabhyang (head massage), Shiropicchu (warm oil application in the ear canal), and Padaabhyang (foot massage). These techniques have proven to be valuable in the treatment of insomnia. In light of recent research findings, it is our aim to delve into the underlying causes, consequences, and potential management strategies for insomnia, all through the unique lens of Ayurvedic wisdom.